Re-thinking of arsiparis as records and archives professional in Indonesia: Case study of Regional Governments - Wahyuni, Elya Riska Dwi; Rakhmawati, Rina (Record and Library Journal, 2024)
Background of the study: To be able to manage archival documents according to applicable standards, organizations need professional and competent arsiparis. Professionalism and competence are represented in the qualification and requirements in the recruitment process. Purpose: This paper aims to present the results of a mapping study of the qualification and special requirement for arsiparis, also analyzes the implications of these aspects for the reinforcement of arsiparis profiles Method: this paper uses an inductive qualitative approach, with the data analysis process by content analysis Findings: Formal educational qualification are still dominant in archival science major, although many opportunities are also for individuals with non-archival science backgrounds. Job experience in archives and records management is also recommended to acquire by individual who wants to be arsiparis. However, these have implications for the arsiparis' profile which tends to be interpreted that archives and records management can be done by anyone. Conclusion: The authors give three recommends. First, confirming educational qualification limits; second, limiting the scope of arsiparis taskforce, and strengthening the independence of professional associations.